JENIS DAN POLA CAMPUR KODE DALAM PERCAKAPAN GURU DAN SISWA PADA WHATSAPP GRUP - Firdaus, Muhammad Anas; Pratiwi, Dini Restiyanti (SASTRANESIA: Jurnal Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2021)
This research was conducted to determine the code mixing patterns contained in the conversation between teachers and students on WhatsApp group class XII SMK Muhammadiyah 2 Andong. This research belongs to a qualitative descriptive study. The data used in the management of this research is in the form of writing, which is in the form of digital communication between teachers and students on the Whatsapp group media. The data sources of this research came from teachers and students of class XII SMK Muhammadiyah 2 Andong. The data were collected using listening techniques, tapping techniques, listening techniques without proficient involvement, and note taking techniques. The data analysis technique used is the BUL technique as the basic technique and the non-parafrasal form changing technique as a follow-up technique. The results of the analysis show that there are 3 type of code mixing with 9 patterns of mixing code in the speech. The code mix is divided into 2 patterns, namely Java-Indonesia-Java and Java-Indonesia-Java-Indonesia-Java-Indonesia. Mix code out is divided into 4 patterns, including: 1) Indonesian-English-Indonesian; 2) Javanese-English-Javanese; 3) English-Indonesian-English-Indonesian-English-Indonesian; 4) English-Javanese-English-Javanese. Meanwhile, mixed code mix was found in 3 patterns, including: 1) Indonesian-Javanese-English; 2) Indonesian-English-Javanese; and 3) Indonesian-English-Indonesian-Javanese.